Integration of English with Professional Cycle Disciplines: Opportunities and Challenges - Hryshchuk, Halyna (Global Prosperity, 2025)
Abstract. The article provides a comprehensive analysis of the problem of integrating the English language with professional cycle disciplines in the system of higher education in Ukraine under conditions of contemporary educational transformations. The relevance of the study is determined by the growing role of English as a tool for professional communication, academic mobility, and access to the international scientific and educational space, as well as by the need to enhance the quality of training of future specialists in the context of European integration processes, digitalisation of education, and socio-psychological challenges caused by wartime conditions. The paper examines the theoretical foundations of integrated learning and generalises contemporary approaches to combining language and professional training. Particular attention is paid to the analysis of the main models of integrating English with academic disciplines, namely EMI, CBI, and CLIL, outlining their didactic potential, advantages, and limitations in the context of Ukrainian higher education. It is demonstrated that the choice of an integrated learning model should be based on the level of learners’ language proficiency, the specifics of professional cycle disciplines, and the methodological readiness of instructors. The article systematises strategies for integrating English with professional cycle disciplines during lectures, practical classes, and seminars, including visualisation, personalisation, historicisation, socio- and linguocultural orientation, diversification of language and speech activities, gamification, collaborative learning, project-based learning, problem-based learning, and the use of information, communication, and multimedia technologies. It is substantiated that the combination of these strategies contributes to reducing cognitive load, increasing learning motivation, and forming professionally oriented foreign language competence. Special attention is given to the key challenges and constraints of implementing integrated learning in current conditions, including the uneven level of English language proficiency among students, increased cognitive load, insufficient methodological training of instructors for integrating language and professional components, as well as the impact of digitalisation and wartime challenges on the educational environment. The significance of the study lies in the possibility of applying the obtained results to improve educational programmes, develop integrated courses, and enhance the quality of professional training in higher education. Prospects for further research are associated with the empirical verification of the effectiveness of integrated learning models and the adaptation of international experience to the needs of Ukrainian higher education.